Web and search engines: A measure of reality? - Aguillo, Isidro F. (Anuario ThinkEPI, 2008)
Although the web has become, as a general rule, the main source of information and its use as a reference source is growing, disproportionate attacks on the reliability of web-based information have been launched from numerous sources, which affects the general public perception of the quality of web content. While recognizing the limitations of the medium, our thesis is that the Web increasingly reflects reality and where this is not the case it is due to omissions or misguided actions by web authors, which in Spain is widening the digital divide.
Keywords: Web; Quality; Reliability; Digital divide.